Effect of spilled diluted bitumen on chemical air-water exchange in boreal lake limnocorrals. (March 2022) - Saunders, Leslie J.; Rodriguez-Gil, Jose L.; Stoyanovich, Sawyer S.; Kimpe, Linda E.; Hanson, Mark L.; Hollebone, Bruce P.; Orihel, Diane M.; Blais, Jules M.
Abstract: Following spills into water, petroleum oils can spread widely and produce surface slicks. Resulting slicks may impede volatilization and possibly increase chemical persistence in water. While the influence of oil films on chemical air-water exchange has been examined through theoretical and laboratory studies, field studies have not been conducted to assess the relevance of these effects following actual oil spill events. Here we evaluated the effect of diluted bitumen (dilbit) experimentally spilled in limnocorrals installed in a boreal lake on the volatilization of sulfur hexafluoride (SF6 ), a non-reactive volatile tracer gas. Dilbit spills were monitored over 70 days and SF6 was introduced twice (after 7 and 48 days) to evaluate the influence of spilled dilbit on the loss of SF6 from water. Volatilization rate constants of SF6 ( k VOL ) significantly decreased by up to 80% with increasing total dilbit spill cover. Using a theoretical equation, decreases in k VOL were largely explained by a reduction in open water area where chemical exchange across the air-water interface occurs. Apparent effects of the slick on SF6 mass transfer were estimated to be smaller by comparison (20%).To account for this reduction in volatilization, oil spill fate models should include a correction to consider the impact of spill cover on the air-water exchange of organic chemicals. Graphical abstract: Image 1 Highlights: The effect of diluted bitumen (dilbit) on the volatilization of sulfur hexafluoride (SF6 ) was evaluated. SF6 volatilization rate constants decreased by up to 80% with increasing dilbit spill cover. Decreases in volatilization were largely explained by a reduction in the open water area where chemical exchange occurs. Oil spill fate models should consider the impeding effect of spill cover on chemical evaporation from water.